2010
DOI: 10.1002/pbc.22806
|View full text |Cite
|
Sign up to set email alerts
|

Educational and vocational achievement among long‐term survivors of adolescent cancer in Germany

Abstract: Most German survivors of cancer during adolescence participate in school and vocational life without major difficulties. Problems particularly arise for survivors with neuropsychological sequelae. Further research should investigate whether these results can be attributed to the German support system for pediatric cancer patients or to sample effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
101
3
10

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(120 citation statements)
references
References 27 publications
6
101
3
10
Order By: Relevance
“…This is an important consideration since middle and late adolescence is defined as ages 15-21 years (Erikson, 1950;Marshall & Tanner, 1974;Nelson et al, 2004). Previous studies of adult survivors of adolescent and young adult (AYA) cancer have described rates of employment (Dieluweit et al, 2011;Parsons et al, 2012;Tai et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important consideration since middle and late adolescence is defined as ages 15-21 years (Erikson, 1950;Marshall & Tanner, 1974;Nelson et al, 2004). Previous studies of adult survivors of adolescent and young adult (AYA) cancer have described rates of employment (Dieluweit et al, 2011;Parsons et al, 2012;Tai et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Successful reentry into work and school may be impacted by neurocognitive morbidities potentially impacting occupational functioning. (Dieluweit et al, 2011) The ability to work has been shown to improve cancer survivors' quality of life, reduce social isolation, and increase self-esteem. Spelten, 2002) A recent study reported that survivors of AYA cancer are significantly more likely to experience disability and unemployment than healthy controls (24% vs. 14%) (Tai et al, 2012); however, it is unclear why this disparity exists and what factors may be associated.…”
mentioning
confidence: 99%
“…Dieluweit et al reported a higher proportion of adolescent cancer survivors who were employed compared to an age-matched sample from the general population [20]. Nevertheless, most of the published studies found the employment rate to be lower among childhood cancer survivors compared with the controls [6,13,[15][16][17][18]29].…”
Section: Discussionmentioning
confidence: 97%
“…Concerning occupational outcomes, most of the studies conducted have reported higher rates of unemployment among childhood cancer survivors than among their siblings or the population as a whole [4,6,[13][14][15][16][17][18]. Factors found to be associated with unemployment risk in the survivor population are both demographic (current age, female gender, interrupted schooling, lower education) [16,17,19,20] and cancerrelated (younger age at diagnosis, treatment with cranial irradiation, somatic late effects) [13,14,[16][17][18][19][20][21][22]. However, when childhood cancer survivors obtain employment, the literature on their occupational achievements is rather sparse.…”
Section: Introductionmentioning
confidence: 94%
“…Les résultats concernant le niveau des études ont été confirmés en GrandeBretagne, où les patients ayant reçu une radiothérapie encépha-lique pour une leucémie, ou suivis pour une tumeur du SNC ont un niveau d'éducation plus faible que les autres [15]. À propos plus spéci-fiquement de l'avenir des adolescents traités entre 15 et 18 ans, leur niveau d'étude est plus élevé que celui de la population générale en Allemagne, ils ont plus souvent un emploi, mais débutent leur activité professionnelle plus tardivement [6]. En Suède, après un cancer pris en charge avant l'âge de 16 ans, le niveau d'éducation est significativement plus faible uniquement pour les patients ayant eu une tumeur cérébrale, et les revenus de ce groupe sont plus bas, y compris après exclusion de ceux touchant une allocation pour handicapé [2].…”
Section: Insertion Socioprofessionnelleunclassified